EU Cohesion Policy and regional club clustering: A comparative analysis of NUTS2 regions in Europe - Leško, Peter; Muchová, Eva; Lešková, Radka (European Spatial Research and Policy, 2026)
This paper assesses territorial cohesion in the EU by examining whether 242 NUTS2 regions converge to a common steady state or form distinct convergence clubs. Using regional GDP per capita data for 2000–2022 and EU Cohesion Policy payments per capita for 2000–2020, we estimate absolute and conditional β-convergence models and apply k-means clustering based on initial income, growth performance, and funding intensity. The results indicate aggregate convergence, but a strongly uneven spatial pattern: regions group into three convergence clubs with different development trajectories. While some initially poorer regions exhibit strong catching-up, other clusters show weak or very slow convergence despite substantial funding. These findings support the Club Convergence hypothesis and underline the need for more place-based cohesion interventions tailored to regional structural conditions.